Digital main line automatic modeling method and system based on large language model - ZHU BIN; YANG SONGGUI; ZHONG ZHAOLIN; YAN YIKANG (2025)
The invention discloses a digital main line automatic modeling method and system based on a large language model, and the system comprises a database system, an embedded model, a vector database, a matching processing unit, a front-end interface, a cue word generation module, and a large language model interface. The digital main line automatic modeling method based on the large language model comprises the following steps: S1, extracting data information of a standard database and a database to be matched and converting formats; s2, storing the data information of the standard database in a vector database in a vectorization manner by using an embedded model; s3, vectorizing to-be-matched business database data information, searching similar fields in a vector database, and selecting candidate fields; s4, the user checks the candidate similar fields and confirms the mapping relation; s5, the data matching relation is input into the large language model, and a data transfer SQL is generated; and S6, executing